The Role of Islam and the Arabic Language in Europe - Ali Ashrafi (IJRAEL: International Journal of Religion Education and Law, 2023)
The article first alludes to the capacities and focal job of the Arabic language, particularly its social job from the start of Islam to the current day. It is then underlined that Islam isn't only a simple conviction framework, yet a legislative, social, lawful, scholarly and creative framework where religion assumes a focal part. These two presents, specifically language and religion, have assumed a significant part in the arrangement of Islamic human progress. The history of science should not be considered as separate from political, social, economic and cultural history. After the initial conquests, Muslims, in accordance with the advice and emphasis of the majority of Islam, began to study science and knowledge and learn from anyone and from anywhere. The Islamic world has influenced medieval Europe in various ways, and this is a fact that many scholars have studied and confirmed, and have presented the results of their studies in this regard in the form of numerous books and articles. The purpose of this study is to first examine the capabilities and central role of the Arabic language, especially its cultural role from the beginning of Islam to the present day, and then the role of this language in science in the middle Ages. The study of scientific interactions between the Islamic world and the West in the early centuries, especially in the field of intellectual sciences and works and their results, constitutes the subject of the present article. The method of this research was documentary analysis and in order to investigate the subject of research, the necessary data were collected and documents related to the subject were analyzed.